Menuju Tercapainya Kemerdekaan Papua Dalam Kerangka Bernegara - Aris Sarjito (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2023)
Since Indonesia gained independence in 1945, security dynamics have been intricately linked with conflict. The emergence of separatist movements, such as the Free Papua Movement or Free Papua Organization (Organisasi Papua Merdeka or OPM), has significantly disrupted Indonesia’s stability. This study aims to analyze the actions undertaken by OPM in their quest for independence, utilizing the perspective of the Montevideo Convention of 1933. Employing a qualitative descriptive research methodology, this research relies on secondary data from a literature review focused on the Papua region. The study reveals several key findings: The size and stability of a population are critical factors for the existence of a state. West Papua, with a population of 1.15 million, plays a pivotal role. The establishment of well-defined territories is crucial for distinguishing and representing nations. The proposed establishment of the Republic of West Papua has garnered support and recognition from nations like Vanuatu. Moreover, the Republic of West Papua actively engages in international organizations such as UNPO. Establishing and exercising effective government control over a nation’s territory is essential for asserting sovereignty and maintaining independence. This is exemplified by the Papua National Manifesto and the declaration of Papua’s independence in 1961. Building and maintaining relationships with other countries necessitate active participation in the global community. International recognition and support play pivotal roles in achieving long-term political goals. Challenges related to democracy, human rights, and environmental issues pose significant hurdles to Indonesia’s diplomatic relations. The Responsibility to Protect (R2P) principle offers a framework for preventing mass atrocities and holding state actors accountable for crimes against humanity. International cooperation and dialogue are imperative in addressing these complex issues and safeguarding the well-being of affected populations.